2018
DOI: 10.1055/s-0038-1660463
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for In-Neonatal Intensive Care Unit Administration of Live, Attenuated Rotavirus Vaccination

Abstract: Rotavirus is the most common nonseasonal vaccine preventable illness. Despite increased severity of rotaviral illness in early infancy, most neonatal intensive care units (NICU) do not administer rotavirus vaccination either during the NICU stay at age of eligibility or at discharge as the Advisory Committee on Immunization Practices recommends. In this commentary, we review the rationale for the administration of rotavirus vaccination to premature infants. Further, we outline data supporting vaccine administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…Hence, this data may mitigate concerns that RV5 vaccination may escalate clinical needs or otherwise complicate admission. 18,19 These results strengthen findings seen in previous pilot studies. 8,9 Goveia et al found no difference in serious adverse events between placebo and RV5, while Roué et al found no difference in serious adverse events between preterm and term infants.…”
Section: Discussionsupporting
confidence: 89%
“…Hence, this data may mitigate concerns that RV5 vaccination may escalate clinical needs or otherwise complicate admission. 18,19 These results strengthen findings seen in previous pilot studies. 8,9 Goveia et al found no difference in serious adverse events between placebo and RV5, while Roué et al found no difference in serious adverse events between preterm and term infants.…”
Section: Discussionsupporting
confidence: 89%